Perlindungan Hukum Atas Surat Keputusan Bupati Jayapura Perihal Tentang Pengosongan Rumah Dan Bangunan Milik Masyarakat (Studi Kasus Putusan Mahkamah Agung Nomor 326 K/TUN/2017) - Dody Surya Lubis (Fakultas Hukum universitas Islam Sumatera Utara, 2020)
AbstractLand is a very basic human necessity. Humans live and carry out activities on land, so that almost all human activities, both direct and indirect, can be conveyed, always available land. Land as a natural resource given by God Almighty to the Indonesian people as a national wealth is a means in the activities of all people and has an important role for humans. The problem that will be examined in this writing is the legal protection of land rights to the community according to Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, Description of the judge's decision regarding the jayapura regent's decree regarding the execution of a community land and building rights , due to the law of the decision of the Supreme Court No. 326 K / TUN / 2017 on the decision of the Regent of Jayapura regarding the emptying of houses and buildings that are subject to state administrative disputes. This research is descriptive with a normative juridical approach.